PROFESSIONAL BURNOUT AMONG HEALTHCARE PROVIDERS TAKING CARE OF PATIENTS WITH DEMENTIA OF DIFFERENT GENESIS - Herasymenko, Larysa; Isakov, Rustam; Orlova, Olga (Eastern Ukrainian Medical Journal, 2025)
Emotional burnout is a prevalent issue among medical and social workers. Healthcare providers attending to patients with various types of dementia are no exception. These caregivers face high levels of physical and emotional stress, constant emotional strain, and the demands of working within a "person-to-person" service system. The sudden onset of the COVID-19 pandemic and the medical community’s lack of preparedness exacerbated these stressors, leading to an increase in both personal and reactive anxiety while performing professional duties. Caregivers engage in continuous, intensive interpersonal contact with patients, creating an emotionally charged environment that significantly contributes to professional burnout. This article examines the prevalence and characteristics of emotional burnout among professional caregivers of patients with dementia of various genesis. The authors emphasize that emotional burnout is not merely a form of stress but a result of a complex interplay of external and internal stress factors within personal and professional relationships. The purpose of the work was to investigate the presence of burnout syndrome among professional caregivers of patients with dementia of various genesis. Using the "Professional burnout" technique (Maslach Burnout Inventory, MBI) in the adaptation of N.E. Vodopyanova examined 87 people who are professional caregivers of patients with dementia of various genesis. Patient care was carried out on a professional basis and was provided by persons with appropriate professional education in the field of medical or social services. In this research, the following professions are represented: psychiatrist, medical psychologist, nurse (medical brother), paramedic (paramedic), social worker. As a result of the examination, mental and physical exhaustion due to long-term emotional stress, which was expressed in a depressed state, fatigue and a feeling of emptiness, a lack of energy and enthusiasm, a loss of the ability to see the positive results of one’s work, a negative attitude regarding work and life in general.